TRPC3 and TRPC6 are essential for normal mechanotransduction in subsets of sensory neurons and cochlear hair cells. Issue 5 (May 2012) - Quick, Kathryn; Zhao, Jing; Eijkelkamp, Niels; Linley, John E.; Rugiero, Francois; Cox, James J.; Raouf, Ramin; Gringhuis, Martine; Sexton, Jane E.; Abramowitz, Joel; Taylor, Ruth; Forge, Andy; et al.
Summary: Transient receptor potential (TRP) channels TRPC3 and TRPC6 are expressed in both sensory neurons and cochlear hair cells. Deletion of TRPC3 or TRPC6 in mice caused no behavioural phenotype, although loss of TRPC3 caused a shift of rapidly adapting (RA) mechanosensitive currents to intermediate-adapting currents in dorsal root ganglion sensory neurons. Deletion of both TRPC3 and TRPC6 caused deficits in light touch and silenced half of small-diameter sensory neurons expressing mechanically activated RA currents. Double TRPC3/TRPC6 knock-out mice also showed hearing impairment, vestibular deficits and defective auditory brain stem responses to high-frequency sounds. Basal, but not apical, cochlear outer hair cells lost more than 75 per cent of their responses to mechanical stimulation. FM1-43-sensitive mechanically gated currents were induced when TRPC3 and TRPC6 were co-expressed in sensory neuron cell lines. TRPC3 and TRPC6 are thus required for the normal function of cells involved in touch and hearing, and are potential components of mechanotransducing complexes.